2022
DOI: 10.1038/s41598-022-24727-z
|View full text |Cite
|
Sign up to set email alerts
|

Apitherapy combination improvement of blood pressure, cardiovascular protection, and antioxidant and anti-inflammatory responses in dexamethasone model hypertensive rats

Abstract: Hypertension-induced ventricular and vascular remodeling causes myocardial infarction, heart failure, and sudden death. Most available pharmaceutical products used to treat hypertension lead to adverse effects on human health. Limited data is available on apitherapy (bee products) combinations for treatment of hypertension. This study aims to evaluate the antihypertensive effects of combinations of natural apitherapy compounds used in the medical sector to treat a variety of diseases. Rats were assigned into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 123 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…A few interesting clinical studies evaluated the effects of BP combinations on the parameters related to metabolic and cardiovascular diseases in humans and generally reported encouraging results including disease-modifying effects in patients with atherogenic dyslipidemia (reviewed in [ 16 , 284 ]), but the pharmacological and clinical relevance of these reports remains to be investigated, since comparative studies or clinical studies of BP alone are still practically absent.…”
Section: Resultsmentioning
confidence: 99%
“…A few interesting clinical studies evaluated the effects of BP combinations on the parameters related to metabolic and cardiovascular diseases in humans and generally reported encouraging results including disease-modifying effects in patients with atherogenic dyslipidemia (reviewed in [ 16 , 284 ]), but the pharmacological and clinical relevance of these reports remains to be investigated, since comparative studies or clinical studies of BP alone are still practically absent.…”
Section: Resultsmentioning
confidence: 99%
“…BV assessed by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay method revealed that its antioxidant activity (depending on the concentration used) is comparable to the activity of vitamin C [95]. The mixture prepared with propolis, royal jelly and BV significantly increased the antioxidative enzymes activity (superoxide dismuthase, SOD; glutathione peroxidase, GPx; and catalase, CAT) with simultaneously decrease in malondialdehyde (MDA, biomarker of unsaturated fatty acids oxidation) level in the dexamethasone model of hypertensive rats [96]. However, this study used the mixture of bee-derived compounds, not only BV, and obtained results could come from other constituents of the mixture.…”
Section: Apoptosismentioning
confidence: 98%